Implementasi Strategi Pemasaran Melalui Media Sosial untuk Meningkatkan Profitabilitas UMKM Gapit Jepit Afisha di Desa Blimbing - Marsningrum, Angela Tiara; Indriani, Vina; Nur Kholis, Novea Isnaini; Diniyah, Wardatud (CV. IRA PUBLISHING, 2025)
This community service study aims to enhance digital marketing capabilities and profitability of Afisha Gapit Jepit MSMEs in Blimbing Village through the utilization of social media. The main challenges include limited market reach, suboptimal marketing strategies, and low adoption of digital technology. A Participatory Action Research (PAR) approach was applied, consisting of problem identification, understanding, planning, action, and monitoring and evaluation. The mentoring focused on managing Facebook, WhatsApp Business, and the Shopee marketplace, including developing promotional content and strengthening the product visual identity. The results show a positive impact: daily sales increased from an average of 40 packages to 80, a 100% increase. The program effectively improved MSME digital capacity and business competitiveness.